2016
DOI: 10.1016/s2352-3026(16)00036-3
|View full text |Cite
|
Sign up to set email alerts
|

Chemoimmunotherapy with methotrexate, cytarabine, thiotepa, and rituximab (MATRix regimen) in patients with primary CNS lymphoma: results of the first randomisation of the International Extranodal Lymphoma Study Group-32 (IELSG32) phase 2 trial

Abstract: Associazione Italiana del Farmaco, Cancer Research UK, Oncosuisse, and Swiss National Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
423
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 494 publications
(447 citation statements)
references
References 29 publications
18
423
2
4
Order By: Relevance
“…The addition of thiotepa to rituximab/HD-MTX/HD-Ara-C further increased response rates in this trial, and there was a trend toward better PFS and OS after a median follow-up of 30 months. 16 Based on a systematic review 5 and our updated MEDLINE search, there is only 1 randomized trial that investigated whether consolidative WBRT (45 Gy) can safely be omitted from HD-MTX without compromising OS (primary end point) in patients with newly diagnosed PCNSL who achieved a CR after induction chemotherapy (Table 1). 6 This non-inferiority trial (N 5 551) had several methodological limitations, including a large number of dropouts or patients lost to follow-up, inconsistencies between perprotocol and intention-to-treat analyses, and an underpowered design.…”
Section: Radiotherapy In Combination With Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of thiotepa to rituximab/HD-MTX/HD-Ara-C further increased response rates in this trial, and there was a trend toward better PFS and OS after a median follow-up of 30 months. 16 Based on a systematic review 5 and our updated MEDLINE search, there is only 1 randomized trial that investigated whether consolidative WBRT (45 Gy) can safely be omitted from HD-MTX without compromising OS (primary end point) in patients with newly diagnosed PCNSL who achieved a CR after induction chemotherapy (Table 1). 6 This non-inferiority trial (N 5 551) had several methodological limitations, including a large number of dropouts or patients lost to follow-up, inconsistencies between perprotocol and intention-to-treat analyses, and an underpowered design.…”
Section: Radiotherapy In Combination With Chemotherapymentioning
confidence: 99%
“…The first randomization investigated the optimal induction treatment 16 and in the second randomization, patients with at least stable disease were randomly allocated between HDT-ASCT and WBRT (N 5 118); final results are pending. 16 A similar trial in the Association des Neuro-Oncologues d'Expression Française/Groupe Ouest-Est d'Étude des Leucémies et Autres Maladies du Sang (ANOCEF/GOELAMS) group (recruitment target, N 5 140) randomized patients after R-MBVP induction to either WBRT with 40 Gy or HDT-ASCT, with results also pending. These 2 studies will provide evidence for the comparison of HDT-ASCT vs WBRT for consolidation in newly diagnosed PCNSL.…”
Section: Ongoing Randomized Trialsmentioning
confidence: 99%
“…Treatment-related clinical neurotoxicity in patients with a sustained CR was more frequent in patients who received WBRT (49%) than in those who did not (26%). In the multicenter randomized phase 2 IELSG-32 trial, 227 newly diagnosed patients with PCNSL were randomized (1: 1: 1) to receive 4 courses of HDMTX and cytarabine (group A) or the same combination along with rituximab (group B) or the same methotrexate-cytarabine-rituximab combination along with thiotepa (group C/MATRix regimen) [14]. Patients with responsive or stable disease after induction chemotherapy were randomly allocated between WBRT and ASCT for consolidation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Prospective randomized trials in adults have demonstrated an improved response rate and PFS when HD-MTX is combined with other chemotherapeutic agents that cross the blood-brain barrier, such as high-dose cytarabine (HD-Ara-C) and thiotepa. 24,25 In most pediatric series, patients with PCNSL have been treated with different chemotherapy regimens; however, common themes exist among these reports (Table 1). In a series of 12 children with PCNSL diagnosed from 1995 to 2003, 10 were treated with chemotherapy alone with a 5-year EFS of 70%.…”
Section: Chemotherapeutic Approaches Systemic Chemotherapymentioning
confidence: 99%
“…A randomized phase 2 trial showed a superior response of the combination of HD-MTX/Ara-C, thiotepa, and rituximab compared with HD-MTX/Ara-C alone, as well as HD-MTX/Ara-C and rituximab. 24 The use of rituximab in systemic B-NHL has been studied in pediatrics in a randomized phase 3 trial. 28 In this study, patients with mature B-NHL were randomly assigned to receive LMB-based chemotherapy with or without rituximab.…”
Section: Rituximabmentioning
confidence: 99%